Maldives : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The Joint Staff Advisory Note report assesses that Maldives has achieved notable development progress through sound macroeconomic management, tourism development, and public service provision improvement under the Poverty Reduction Strategy Paper (PRSP). Executive Directors emphasized the need to strengthen the fiscal policy framework, develop institutions, implement structural reforms and a realistic budget to mitigating risks, and ensure macroeconomic stability. Directors welcomed the Seventh National Development Plan, the new Poverty Reduction Strategy Paper, and stressed the need for significant efforts to ensure the successful implementation of the economic development program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet